Structure-based Virtual Screening, and Design of Some Lead Compounds as Inhibitors of Kras-G12D of Pancreatic Cancer - Ovaku, Idris Momohjimoh; Abechi, Stephen Eyije; Shallangwa, Gideon Adamu; Umar, Abdullahi Bello; Uzairu, Adamu (Indonesian Society for Cancer Chemoprevention, 2024)
Pancreatic cancer is an abnormal cell growth in the pancreas. In 2021, approximately 60,430 individuals were diagnosed in the USA, with the annual increasing incidence rates. Pancreatic cancer is anticipated to become the second leading cause of cancer mortality by 2030. This escalating challenge has prompted a search for innovative therapeutic agents. Virtual screening, a computational technique, was employed to discover novel drug-like compounds from a diverse set of 30 chemical compounds, sourced from the PubChem database. These compounds were evaluated based on some important properties, including pharmacokinetics, lipophilicity, drug-likeness, water-solubility, and physicochemical characteristics. Seventeen compounds emerged as promising candidates for pancreatic cancer treatment. Subsequent molecular docking studies focused on the Kras-G12D protein target and identified Ligand 18 as the leading candidate, exhibiting a binding energy (BE) of -10.5 kcal mol-1 and extensive interactions with the target protein. Additionally, a newly designed compound, D4, displayed an even higher BE of -10.8 kcal mol-1, fitting more effectively into the protein's binding site than existing drugs like Gemcitabine and Irinotecan. All newly designed compounds met the five scientists' rule, indicating favorable drug-likeness and bioavailability. These findings pave the way for developing a new generation of less toxic therapeutic compounds for pancreatic cancer treatment.Keywords: virtual screening, binding energy, kras-G12D, pancreatic cancer, designed compounds.